Training on the Production and Use of Organic Liquid Fertilizer for the Community in Suka Merindu Village to Support of Environmentally Friendly Agriculture - Eka Mulyana; Ardi Saputra; Reno Mardhotillah (Unram Journal of Community Service, 2025)
This community service program aimed to enhance community capacity in producing and utilizing organic liquid fertilizer to support environmentally friendly agricultural practices in Suka Merindu Village, West Pemulutan Subdistrict, Ogan Ilir Regency. The activity was conducted using a participatory approach that positioned the community as active participants throughout the process. The program stages included initial socialization with community leaders, identification of local potential and problems through focus group discussions, hands-on training on organic liquid fertilizer production using locally available organic waste, and post-training mentoring and monitoring to ensure sustainability. The results indicate that the training program effectively improved participants’ knowledge and technical skills, as evidenced by a substantial increase in post-test scores compared to pre-test results. Participants also reported high levels of satisfaction with the training materials, facilitation, and practical sessions. Furthermore, most participants began applying organic liquid fertilizer in their farming practices, demonstrating the practical relevance and sustainability of the program outcomes. In addition to technical improvements, the activity increased community awareness of the environmental and economic benefits of reducing dependence on chemical fertilizers and utilizing organic waste more productively. Overall, this community service program demonstrates that participatory training on organic liquid fertilizer production can serve as an effective strategy for promoting sustainable agriculture, strengthening farmers’ economic resilience, and encouraging environmentally responsible resource management in rural areas.